Comparison of Forensic Tool Results on Android Smartphone Backup Files Using NIST Method (Universitas Ahmad Dahlan, 2022)
Smartphone technology currently developing not only has a positive impact but can also have a negative impact if it is used to commit crimes which can be called cybercrime. Choosing the right forensic tools is very important when conducting an investigation. So it is necessary to research the results of the comparative analysis of the performance of forensic tools on android smartphone backup files. The National Institute of Standards and Technology (NIST) method was used in this study as a parameter and for the digital evidence obtained. The results of the extraction of the OPPO A37f android smartphone from the MOBILedit tools acquired android backup files and the analysis results from using the Magnet AXIOM tools with a data accuracy rate of 39.3% from the predetermined variables. The Oxygen Forensic Tools obtained a data accuracy rate of 28.6% from the variable that has been determined. The Belkasoft Evidence Center tools can get a data accuracy rate of 35.7% of the predetermined variables. The results of this study can be concluded that the Magnet Axiom tool has a high level of accuracy compared to the Oxygen Forensic and Belkasoft Evidence Center tools in extracting data from android smartphone backup files.